PROSES KREATIF PENCIPTAAN TARI TIGA SERANGKAI OLEH KUSMINDARI TRIWATI DI SANGGAR ANDARI KOTA PONTIANAK - Putri, Selly Yulia; Ismunandar, Ismunandar; Satrianingsih, Aline Rizky Oktaviari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Understanding the process of creating the Kusmindari Triwati dance and the choreography of the Tiga Serangkai Dance is the driving force for this research. This type of research uses a choreographic approach with a qualitative and descriptive approach. Interviews with informants, documentation studies, and observations were used to collect data in this research. Source triangulation is a method for evaluating the reliability of data. Kusmindari Triwati's creative process in creating the Tiga Serangkai Dance and its choreography is the subject of this research. Based on the research results, it can be said that Kusmindari Triwati created the Tiga Serangkai Dance in 2003 for the Kalimantan Cultural Festival. The creation of the Tiga Serangkai Dance went through the exploration stages of Dayak movements such as kenyalang, stomping, sirang, and ngajat iban. Malay tiung jumping and gersik steps. and Chinese movements si liu bu, fu hu bu or pu bu, and xuun ji bu or xiu bu. develop traditional movements that have a unified subject. The improvisations are based on the activities of the Dayak, Malay and Chinese communities. The Tiga Serangkai dance has a theme of inter-ethnic unity and unity, which is danced by an even number of female dancers accompanied by the musical instruments sape, tuma, kubeh, soleng, beruas, tambourine, accordion, gambus, tar, Chinese drum and cymbals.